A Comparative Analysis of Recent MPPT Algorithms (P&O\INC\FLC) for PV Systems - Maamar, Yahiaoui; Elzein, I. M.; Benameur, Afif; Mohamed, Horch; Mahmoud, Mohamed Metwally; Mosaad, Mohamed I.; Shaaban, Salma Abdelaal (Journal of Robotics and Control (JRC), 2025)
Although solar (PV) power generators have been widely deployed, one important barrier to their effective energy capture is weather variability. It is a very challenging effort for these systems to operate at MPPT. Conventional MPPT methods still had an excessively long convergence period to the MPP. Because of their superior data processing, intelligent approaches are nevertheless given a reasonable length of time to reach the maximum point, beginning with the objective of keeping the PV generator in the MPP with outstanding performance. To accomplish MPPT, a comparison between intelligent (fuzzy control (FLC)) and conventional algorithms (perturb-and-observe (P&O) and the incremental conductance (INC)) is investigated. To do this, a mathematical model of PV cells based on two diodes with shunt and series resistors is created with MATLAB/Simulink. The model characteristics curves with the parameters listed in the MSR SOLAR datasheet are compared. Finally, we compared the results of the FLC with those of the P&O and the INC. The results obtained demonstrated the superiority of the FLC-MPPT controller.